Removal of pharmaceutical and personal care products (PhPCPs) using different low-cost materials as substrates in the vertical, horizontal, and hybrid flow systems of constructed wetland ? A review - Alsalihy S.T.H.; Ahmed A.N.; Salih G.H.A.; M-Ridha M.J.; Falahi O.A.A. (Elsevier B.V., 2025)
An increasing number of people are starting to worry about pharmaceutical chemicals in wastewater due to the widespread use of pharmaceuticals in human activities. Nevertheless, wastewater treatment technology has a hurdle when dealing with pharmaceutical residues. Wastewater treatment facilities (WWTPs) are one area where a thorough overview of PhPCPs removal methods is lacking. Wastewater (WW) treatment options abound, but we urgently need cost-effective, long-term solutions. To address the concerning presence of PhPCPs in wastewater treatment, this paper summarises and reviews the comprehensive evaluation of all techniques of removal of PhPCPs in wastewater treatment physical, chemical and biological. Phytotechnology used to remove them by constructed wetlands (CWs) using a range of substrates, including the more traditional gravel and sand, as well as different types of waste, including cellulosic, industrial, animal, and mineral waste. In addition to contributing to the resolution of the ?waste? issue, the economic benefits of reusing waste materials such as cellulose waste, sludge from water treatment, animals manure, and sewage treatment sludge are substantial. We assess the efficacy of PhPCP phytoremediation by analysing the operational parameters for phytotechnology deployment, including substrate, concentration, species, types of CWs, and retention duration. The findings provided further evidence that CWs should be used as a tertiary treatment at WWTPs to prevent the spread of PhPCPs and their high frequency in the environment. ? 2024 The Authors